Traceability of DC and AC high voltage measurements using voltage divider calibration. Issue 2 (April 2018) - Abdel Mageed, Hala M; Alenezi, Faisal Q
This paper focuses on achieving traceability of high voltage measurements up to 200 kV at the Egyptian National Institute of Standards. The measurement system consists of an AC/DC voltmeter and a universal resistive/capacitive high voltage divider. The voltmeter shows measured voltage values based on the scale factor of the voltage divider. The divider ensures a stable capacitance for AC voltage measurements and an additional resistive parallel path for DC voltage measurements. Both the divider and the voltmeter are calibrated in AC and DC modes. All uncertainty components are taken into account to obtain measured values with an acceptable accuracy. The calibration results in traceability to the national standards, which make measurements using the international system of units. The proposed calibration method is useful for the theory and practice of high voltage measurements in education, industrial applications, and electrical metrology studies.